Iron Age farming in the Central European Alpine and Dinaric regions; crop occurrence and distribution - Paušič, Andrej; Šušek, Andrej (Agricultura Scientia, 2020)
The main objective of this paper was to holistically describe the occurrence of most important crop taxa found in different archaeological Iron Age sites in two selected biogeographical regions of Central Europe; in the Alpine and the Dinaric mountains. This study also links the known results of research about the ecological-biogeographical conditions in the Central Europe during the Iron Age time with the papers that include archaeobotanical data of the selected European landscapes as well. It is evident that many factors played crucial roles in the domestication process of many different plant taxa. This study showed that both the Alpine and the Dinaric region of Europe show similar ecological conditions for successfully growing important legumes and cereal taxa. The percentage of found cereal taxa is higher in the Dinaric region as it is in the Alps. In most archaeological sites in the Dinaric mountains, there were no evidence of the productionof pulses at all. However, if comparing the whole repertoire of cultivated plant taxa in the Iron Age epoch in both studied regions, one can conclude that there is not much difference in the number of cultivated planted taxa in the Iron Age epoch.
Keywords: archaeobotany; biogeography; crop domestication; Iron Age; palaeoenvironmental research